A theoretical investigation into the role of catalyst support and regioselectivity of molecular adsorption on a metal oxide surface: NO reduction on Cu/γ-alumina. Issue 4 (11th December 2020) - Ota, Wataru; Kojima, Yasuro; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro; Sato, Tohru
Abstract : The role of catalyst support and regioselectivity of molecular adsorption on a metal oxide surface is investigated for NO reduction on a Cu/γ-alumina heterogeneous catalyst. Abstract : The role of catalyst support and regioselectivity of molecular adsorption on a metal oxide surface is investigated for NO reduction on a Cu/γ-alumina heterogeneous catalyst. For the solid surface, computational models of the γ-alumina surface are constructed based on the Step-by-Step Hydrogen Termination (SSHT) approach. Dangling bonds, which appear upon cutting the crystal structure of a model, are terminated stepwise with H atoms until the model has an appropriate energy gap. The obtained SSHT models reflect the realistic infrared (IR) and ultraviolet-visible (UV/Vis) spectra. Vibronic coupling density (VCD), as a reactivity index, is employed to elucidate the regioselectivity of Cu adsorption on γ-alumina and that of NO adsorption on Cu/γ-alumina in place of the frontier orbital theory that could not provide clear results. We discovered that the highly dispersed Cu atoms are loaded on Lewis-basic O atoms, which is known as the anchoring effect, located in the tetrahedral sites of the γ-alumina surface. The role of the γ-alumina support is to raise the frontier orbital of the Cu catalyst, which in turn gives rise to the electron back-donation from Cu/γ-alumina to NO. In addition, the penetration of the VCD distribution of Cu/γ-alumina into the γ-alumina support indicates that the excessive reaction energy dissipates into the support after NO adsorption and reduction. In other words, the support plays the role of a heat bath. The NO reduction on Cu/γ-alumina proceeds even in an oxidative atmosphere because the Cu–NO bond is strong compared to the Cu–O2 bond.